New acetylenic metabolites from the toxic mushroom Tricholoma pardinum - Clericuzio, Marco; Hussain, Faiq H S; Amin, Hawraz Ibrahim M; Salis, Annalisa; Damonte, Gianluca; Pavela, Roman; Vidari, Giovanni (Natural product research, 2021)
Four unprecedented acetylenic alcohols, (Z)-non-7-en-5-yn-1,2,4-triol (1), (Z)-non-7-en-5-yn-1,4-diol (2), (Z)-1,2-dihydroxynon-7-en-5-yn-4-one (3), and (Z)-1-hydroxynon-7-en-5-yn-4-one (4) were isolated from the poisonous mushroom Tricholoma pardinum (Agaricales, Basidiomycota), together with the known compounds 1H-indole-3-carbaldehyde (5) and 6-hydroxy-1H-indole-3-carbaldehyde (6). Their structures were determined by NMR and IR spectroscopy, and mass spectrometry. The crude acetone extract of the mushroom showed potent anti-arthropod activity against Tetranychus urticae (Acarinae), a dangerous crop pest.[Figure: see text].
Keywords: acetylen; Tricholoma; Agaricales; hmotnostní spektrometrie; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; Mass Spectrometry; Acetylene